Short Communication: The potential of secondary metabolites of Myrmecodia tuberosa from different host trees - YANTI PUSPITA SARI; WAWAN KUSTIAWAN; SUKARTININGSIH SUKARTININGSIH; AFIF RUCHAEMI (Smujo International, 2017)
Sari YP, Kustiawan W, Sukartiningsih, Ruchaemi A. 2017. Short Communication: The potential of secondary metabolites of Myrmecodia tuberosa from different host trees. Nusantara Bioscience 9: 170-174. Ant-plants (Myrmecodia tuberosa Jack.) is a medicinal plant that could potentially inhibit cancer cell growth. Ant-plants is epiphytic plants whose commonly life was attached to the host tree. Several information from local people stated that ant-plants attaching to different host trees possesses different active compounds. The purpose of this study was to determine the secondary metabolites of each parts of ant-plants including leaves, stems and tubers from different tree hosts i.e mango and durian. Result from phytochemical analysis showed that ant-plants living in mango and durian trees positively contained the metabolic compounds including phenolics, flavonoids, alkaloids, saponins and steroid/triterpenoid. The Total of Phenolic Content (TPC) and the Total of Flavonoids Content (TFC) on the leaves of ant-plants was higher than that in tubers or stems of ant-plants derived from both host trees i.e mango and durian. The value of TPC and TFC of the ant-plants leaves derived from the durian host tree (319.33 ± 0.06 mg GAE/g and 272.33 ± 0.02 mg CE/g) was higher than those from mango host trees (172.80 ± 0.02 mg GAE/g and 162,83 ± 0.01 mg CE/g). Ant-plants, whose life was attached to a different host tree, had the same content of secondary metabolites although those quantities were different in each host trees. Therefore, ant-plants from different host trees could be used as a medicinal plant by concerning the amount of used extract for effectiveness medicinal purposes.